"Who Do These People Want Teaching Their Children?" White Saviorism, Colorblind Racism, and Anti-Blackness in "No Excuses" Charter Schools. (November 2022) - Sondel, Beth; Kretchmar, Kerry; Hadley Dunn, Alyssa
In this article, we explore how White supremacist ideologies operate in "no excuses" charter schools. Drawing on critical race frameworks and qualitative data collected in two "no excuses" charter schools in New Orleans, we illustrate how anti-Blackness, White saviorism, and colorblind racism are taken up through hiring practices, discipline policies, and school culture. Collectively, these constructs are used in efforts to justify the mistreatment of Black students. We argue that it is the presence of an elite network of entrepreneurial organizations that have gained power over schools through corporate reform that allows for this unbridled racism.